Catheter ablation of idiopathic ventricular tachycardia in children using the EnSite NavX system with/without fluoroscopy. (10th September 2013) - Ozyilmaz, Isa; Ergul, Yakup; Akdeniz, Celal; Ozturk, Erkut; Tanidir, Ibrahim C.; Tuzcu, Volkan
Abstract Objectives Curative therapy of idiopathic ventricular tachycardia remains a challenge in interventional electrophysiology. The aim of this study was to demonstrate the utility of an EnSite NavX system in the catheter ablation of idiopathic ventricular tachycardia in children. Patients and methods In all, 17 children with idiopathic ventricular tachycardia underwent electrophysiological studies using the EnSite NavX system guidance. Results The mean patient age was 13 ± 2.4 years (range: 7.8–17.9) and the mean patient weight was 52.3 ± 11.9 kg (range: 32–75). The origin of ventricular tachycardia was in the right ventricular outflow tract in nine patients, in the left ventricle in six, near the bundle of His/right bundle branch in one, and in the left aortic cusp in one. The mean procedure and fluoroscopy times were 169.3 ± 43.2 minutes and 8 ± 10.8 minutes, respectively. No fluoroscopy was used in six patients. The mean radiation exposure was 33.1 ± 56.4 mGy. Acute success was achieved in 14 patients (82%). The focus of ventricular tachycardia was epicardial in two failed procedures. During a mean follow-up of 8.5 ± 7.6 months, ventricular tachycardia recurred in three patients, two of whom underwent a second procedure. Except for one patient who developed transient right bundle branch block, no complications were seen. Conclusion Catheter ablation of idiopathic ventricular tachycardia in children can be performed safely and effectively with low fluoroscopy exposure using the EnSite NavX system.